Condition assessment of pre-tensioning prestressed concrete sleepers distressed by internal swelling reactions (ISR) - R. Medeiros; D.J. De Souza; L.F.M. Sanchez; A.C. Santos (Cement)
Concrete sleepers worldwide have been affected by internal swelling reactions (ISR), primarily alkali-silica reaction (ASR) and internal sulfate attack (ISA). While numerous studies have focused on diagnosing ISR-affected sleepers, most emphasize identifying the cause rather than estimating the extent of deterioration, which is critical for informed decision-making. This study presents a comprehensive condition assessment of concrete sleepers displaying numerous ages and environmental exposure conditions through visual inspection (i.e., crack measurements) followed by the implementation of the multi-level assessment protocol, composed of microscopic (i.e., damage rating index-DRI) and mechanical (i.e., stiffness damage test-SDT) testing procedures. Results evidenced the multi-level protocol efficiency in estimating the cause(s) (i.e., ASR+ISA), further confirmed through SEM-EDS analysis, and quantifying the deterioration extent. These findings reveal gaps in current specification to prevent ISR damage in new sleepers and the importance of considering environmental conditions in condition assessment of existing sleepers, demonstrating an urgent need to review specifications/protocols.